TNF-α modulates cell proliferation via SOX4/TGF-β/Smad signaling in benign prostatic hyperplasia - Jinze Li; Bo Chen; Yin Huang; Xinyang Liao; Jia You; Zeyu Chen; Shu Ning; Asmaa Reda; Junwei Zhao; Biao Ran; Jingxing Bai; Mengli Zhu; et al. (Cell Death and Disease)
Abstract Benign prostatic hyperplasia (BPH) is an age-related condition in men with a poorly defined etiology. Chronic inflammation is increasingly recognized as a key contributor to BPH progression; however, the underlying mechanisms remain incompletely understood. This study aimed to elucidate the role of a TNF-α-induced inflammatory microenvironment in regulating BPH progression. We demonstrated that TNF-α levels were significantly elevated in patients with BPH and positively correlated with key clinical characteristics. In vitro, TNF-α promoted the proliferation of prostatic cells. Mechanistically, TNF-α induced the overexpression of SOX4, which subsequently activated the TGF-β/Smad2/3 signaling axis, thereby enhancing cellular proliferation, promoting epithelial-mesenchymal transition (EMT), and exacerbating fibrosis. Importantly, metformin (Met) treatment reduced the expression levels of relevant inflammatory cytokines in the serum of BPH rats. Further analysis confirmed that Met inhibited the TGF-β/Smad2/3 signaling pathway by downregulating the expression of SOX4, thus suppressing cell proliferation, reversing EMT, alleviating fibrosis, and ultimately exerting anti-BPH effects. Collectively, our findings suggest that TNF-α promotes BPH progression via activation of the SOX4/TGF-β/Smad2/3 axis, while Met exerts therapeutic effects by targeting this pathway. These results highlight SOX4 as a potential therapeutic target for BPH and support the clinical potential of Met in BPH management.